Analisis Pengaruh Parameter Pengelasan terhadap Heat Input pada Proses GTAW Multipass Pipa ASTM A36 - Maryadi, Maryadi; Zulfikar, Muhammad; Arifiansah, Arifiansah; Farudin, Tugiman (CV. IRA PUBLISHING, 2026)
This research aims to evaluate heat input calculations in multipass Gas Tungsten Arc Welding (GTAW) on ASTM A36 steel pipe. The primary parameters investigated include current, voltage, and welding speed, incorporating a process efficiency factor (η = 0.7). The research methodology employs an experimental approach where heat input values are systematically calculated for each welding layer. The results indicate that increases in current and voltage are directly proportional to the rise in heat input, whereas an increase in welding speed is inversely proportional to it. Specifically, the highest heat input was observed in the root layer at 2.43 kJ/mm, followed by the filler layer (2.20 kJ/mm), capping layer (2.08 kJ/mm), and hot pass layer (2.00 kJ/mm). Metallurgically, these findings indicate that excessive heat input can trigger grain growth in the Heat Affected Zone (HAZ), while insufficient heat input can lead to lack-of-fusion defects. This study significantly contributes to understanding thermal energy distribution across multipass welding layers, providing a fundamental basis for determining optimal parameters to ensure high-quality weld joints.